2018
DOI: 10.1002/erv.2654
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in the EEG power spectrum in bulimia nervosa, binge‐eating disorder, and obesity: A systematic review

Abstract: To provide a basis for electroencephalography (EEG) neurofeedback protocols for bulimia nervosa (BN), binge‐eating disorder (BED), and obesity, this systematic review investigates alterations in EEG‐measured brain activity, specifically frequency bands. A systematic literature search with predefined search terms yielded N = 7 studies meeting the inclusion criteria. The risk of bias was assessed for all studies. In resting‐state EEG, the beta activity was elevated in fronto‐central regions in individuals with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 65 publications
3
35
0
Order By: Relevance
“…Still, according to the results of the present study, physiological changes seem to play a role in this NF protocol against binge eating, linking reduced cortical arousal to less craving and less frequent binge eating episodes (Blume et al 2019 ; Parvaz et al 2011 ). This finding is also important because EEG high beta activity has seldom been the main target frequency range in NF protocols (Paquette et al 2009 ; Zotev et al 2014 ), but has instead mostly been used as a supplementary control range (Egner and Gruzelier 2001 ; Keith et al 2015 ).…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Still, according to the results of the present study, physiological changes seem to play a role in this NF protocol against binge eating, linking reduced cortical arousal to less craving and less frequent binge eating episodes (Blume et al 2019 ; Parvaz et al 2011 ). This finding is also important because EEG high beta activity has seldom been the main target frequency range in NF protocols (Paquette et al 2009 ; Zotev et al 2014 ), but has instead mostly been used as a supplementary control range (Egner and Gruzelier 2001 ; Keith et al 2015 ).…”
Section: Discussionsupporting
confidence: 56%
“…Besides these methodological suggestions, the scientific rigor of RCTs on NF treatments should further be improved by preregistration of NF studies to prevent false-positive results and underreporting of negative outcomes in NF research (Ros et al 2020;Thibault et al 2018). Still, according to the results of the present study, physiological changes seem to play a role in this NF protocol against binge eating, linking reduced cortical arousal to less craving and less frequent binge eating episodes (Blume et al 2019;Parvaz et al 2011). This finding is also important because EEG high beta activity has seldom been the main target frequency range in NF protocols (Paquette et al 2009;Zotev et al 2014), but has instead mostly been used as a supplementary control range (Egner and Gruzelier 2001;Keith et al 2015).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…During the last decades, an increasing number of studies focused on the neuronal basis of obesity, mostly based on functional magnet resonance imaging or electroencephalography (EEG, for reviews see References [1,2,3]). Consistently, neuroimaging studies revealed altered neurophysiological processes in the orbitofrontal cortex [4,5,6], a region crucial for reward and reinforcement processes [7], and the dorsolateral prefrontal cortex, which is known to be involved in cognitive control [8,9,10], particularly in the processing of food cues [11].…”
Section: Introductionmentioning
confidence: 99%